Lumbar Puncture Opening Pressure in Patients with Spinal Muscular Atrophy - Becker, Lena-Luise; Weiß, Claudia; Tietze, Anna; Martiny, Viktoria; Kaindl, Angela M. (Neuropediatrics, 2021)
The announcement of a hydrocephalus as a possible side effect in patients with spinal muscular atrophy (SMA) receiving the drug nusinersen, promoted major concern and warrants further evaluation. In this retrospective monocentric study, we analyzed clinical data, lumbar puncture opening pressure (LOP) measurement, and ophthalmologic and neuroimaging results in 34 patients with SMA types 1 to 3 undergoing treatment with nusinersen. None of the patients reported symptoms indicative of increased intracranial pressure. In our cohort, the LOP was >20 cm H2O in 25 patients (70.5%), and within this group ≥28 cm H2O in 12 patients (35.3%), in two patients, it was increased prior to treatment initiation. Signs of increased intracranial pressure in ophthalmological assessments or brain imaging were only seen in one patient. We did not identify a correlation between increased LOP and SMA type, scoliosis, or age of the patients; however, it was slightly higher in patients receiving sedation. Our results raise the question whether the LOP is generally increased in SMA as part of the underlying disease, if so, what the etiology is, and whether the increased LOP needs to be treated.
Keywords: spinal muscular atrophy; intracranial pressure; nusinersen; hydrocephalus; MRI; lumbar puncture opening pressure